Multi-effect nanoemulsion and preparation method, use method and application thereof
By using the single -phase slow -speed acid system prepared by multi -efficiency nano -emulsion, the problem of depth uniform and acidification and reservoir damage in the acidification of carbonate rock reservoir reservoir reservoirs is solved, and high slow speed, low rubber resistance and low damage are achieved The acidification effect.
Patent Information
- Application Number
- CN202310692778.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-06-12
AI Technical Summary
The existing acid-pressure technology for acid-pressing of carbonate reservoirs is difficult to achieve deep uniform acidification, and the acid liquid causes damage to the reservoir, which has problems such as high friction resistance and residue damage.
The single -phase slow -speed acid system prepared by multi -effect nano -emulsion is used. This system includes oil nucleus, surfactants, alcohol and water containing long chain or cyclocarboxylic acids. Etatoscopic, iron ion stabilizers, emulsifiers, resistance, and water forming a single -phase slow acid system.
The performance of high slow rate, low rubber resistance and low damage can be achieved, can deeply acidify acid pressure, reduce reservoir damage, improve the diversion ability of acid erosion cracks, and can simultaneously dissolve organic and inorganic dirt.
Smart Images

Figure CN116731698B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbonate reservoir acidizing and fracturing, and relates to a multi-effect nanoemulsion and a preparation method, a use method and an application thereof, and in particular to a multi-effect nanoemulsion for a single-phase slow acid system and a preparation method, a use method and an application thereof. Background Art
[0002] Carbonate reservoirs have a fast acid-rock reaction rate, and the reservoirs often have developed caves and cracks, strong heterogeneity, large filtration loss, and limited acid action distance. To achieve an ideal production increase effect, deep acidizing / acid fracturing transformation must be achieved. At present, the development trends of carbonate reservoir acidizing and acid fracturing technology at home and abroad mainly include the following three aspects: ① How to achieve comprehensive and uniform acidification of heterogeneous reservoirs in two dimensions, that is, how to effectively acidify reservoirs with different permeabilities and different degrees of damage in heterogeneous oil and gas reservoirs in both vertical and horizontal directions; ② Deep acidification to reduce the acid-rock reaction rate and increase the effective action distance of acid etching; ③ Avoid or reduce the damage to the reservoir caused by the acidizing process itself.
[0003] Chinese invention patent CN104194767A discloses a high temperature resistant emulsified acid solution, and its technical solution forms a high temperature emulsified acid system by selecting an efficient emulsifier, but the emulsified acid has the problems of high friction and high construction pump pressure. Chinese invention patent CN107974246A discloses a high temperature resistant cross-linked acid system, preparation method and application. The cross-linked acid system for high temperature resistant acid fracturing of the invention can be applied to the acid fracturing transformation of high temperature carbonate reservoirs. However, the cross-linked acid system has a high residue content and causes great damage to the reservoir. Chinese invention patent CN114316935A discloses a microlactic acid unblocking system and its preparation method. The microlactic acid unblocking system provided by the invention has the characteristics of slow reaction speed, strong dissolution ability and friendly environmental interface, and has a good unblocking effect on inorganic and organic blockages in the formation, but the system uses organic acid for deceleration, and the cost of organic acid is relatively high, and the organic acid has limited dissolution ability for carbonate rocks.
[0004] The emulsified acid system emulsifies hydrochloric acid in the oil phase to form a physical isolation interface, which reduces the rate at which the acid diffuses to the surface of carbonate rocks. It has the advantages of deep dissolution and low damage, and is less corrosive to construction equipment and pipes. However, the high friction of emulsified acid results in high construction pump pressure and low displacement, which limits the acidizing and acid fracturing effect. The thickened acid system uses the high viscosity of polymers to reduce the transfer rate of hydrogen ions to the rock wall. It has the advantages of slow speed and low friction, but the residual acid in the thickened acid system will cause a certain degree of damage to the reservoir. The development of a new acid system that has slow speed, low friction and low damage performance is of great significance for the acidizing and acid fracturing transformation of carbonate reservoirs. Summary of the invention
[0005] The purpose of the present invention is to provide a multi-effect nanoemulsion and a preparation method, a use method and an application thereof in view of the defects of the prior art.
[0006] Specifically, the multi-effect nanoemulsion provided by the present invention comprises, by weight percentage: 5%-15% of an oil core containing a long-chain or cycloalkyl carboxylic acid, 30%-50% of a surfactant, 10%-30% of an alcohol and the remainder of water.
[0007] In the above-mentioned multi-effect nanoemulsion, the long-chain or cycloalkyl carboxylic acid includes one or more of oleic acid, cyclohexylacetic acid, cyclohexylpropionic acid, and cyclohexylvaleric acid; and the oil core includes one or more of cyclohexane, limonene, and high-flash point heavy aromatic hydrocarbons.
[0008] In the above-mentioned multi-effect nanoemulsion, the surfactant includes one or more of tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, fatty alcohol polyoxyethylene ether, sodium lauryl sulfate, and styrylphenol polyoxyethylene ether.
[0009] In the above-mentioned multi-effect nanoemulsion, the alcohol includes one or more of n-pentanol, isopropanol, propylene glycol and n-octanol.
[0010] On the other hand, the present invention also provides a method for preparing the above-mentioned multi-effect nanoemulsion, comprising the following steps:
[0011] (1) In a reaction kettle, an oil core containing a long-chain or cycloalkyl carboxylic acid, alcohol and water are added according to a ratio;
[0012] (2) slowly adding the surfactant into the reaction kettle and stirring slowly;
[0013] (3) The reactor is sealed, stirring and heating are continued, and cooling is performed after the dissolution is complete to obtain a multi-effect nanoemulsion.
[0014] In the above-mentioned method for preparing the multi-effect nanoemulsion, the heating temperature is 40-60°C.
[0015] In the above-mentioned method for preparing the multi-effect nanoemulsion, the cooling temperature is below 30°C.
[0016] On the other hand, the present invention also provides a method for using the above-mentioned multi-effect nanoemulsion, comprising: mixing the multi-effect nanoemulsion, hydrochloric acid, corrosion inhibitor, iron ion stabilizer, demulsifier, resistance reducing agent and water in proportion, and stirring at 10-40° C. for 0.5-1 hour to obtain a single-phase slow acid system.
[0017] The method for using the above-mentioned multi-effect nanoemulsion is as follows: the single-phase retarding acid system comprises, by weight percentage: 1%-20% of the multi-effect nanoemulsion, 5%-25% of hydrochloric acid, 0.5%-3% of the corrosion inhibitor, 0.5%-2% of the iron ion stabilizer, 0.5%-2% of the demulsifier, 0.1%-0.8% of the resistance reducing agent and the balance of water.
[0018] In the method for using the above-mentioned multi-effect nanoemulsion, the corrosion inhibitor comprises: one or more of pyridine quaternary ammonium salt corrosion inhibitors, quinoline quaternary ammonium salt corrosion inhibitors and imidazoline corrosion inhibitors.
[0019] In the method for using the above-mentioned multi-effect nanoemulsion, the iron ion stabilizer includes: one or more of citric acid, ethylenediaminetetraacetic acid and isoascorbic acid.
[0020] In the method for using the above-mentioned multi-effect nanoemulsion, the demulsifier includes: one or more of sodium dioctyl sulfonate, polyoxyethylene ether, and dialkyl succinate.
[0021] In the method for using the above-mentioned multi-effect nanoemulsion, the drag reducing agent comprises one or more of cationic polyacrylamide, polysaccharide polymer and vinyl polymer.
[0022] In another aspect, the present invention also provides the use of the multi-effect nanoemulsion in acidizing and fracturing of carbonate reservoirs.
[0023] The technical solution of the present invention has the following beneficial effects:
[0024] (1) The single-phase retarding acid system prepared by the multi-effect nanoemulsion of the present invention has a high retarding rate performance, with a retarding rate of more than 90%, and can realize deep acidification and acid fracturing of carbonate reservoirs;
[0025] (2) The single-phase slow-rate acid system prepared by the multi-effect nanoemulsion of the present invention has low friction resistance, and the drag reduction rate is above 70%, which can realize large-volume acidizing and fracturing operations in carbonate reservoirs;
[0026] (3) The single-phase slow acid system prepared by the multi-effect nanoemulsion of the present invention has low damage performance. The system contains only 0.1%-0.8% of polymer drag reducing agent, the polymer content is low, and the damage rate of residual acid to the core is much lower than that of thickened acid; and the multi-effect nanoemulsion has low surface interfacial tension, which can relieve water lock damage, and the damage rate of residual acid to the core is even lower than that of emulsified acid;
[0027] (4) The single-phase slow acid system prepared by the multi-effect nanoemulsion of the present invention has a nano-particle size, which can enter the small-sized pores in the carbonate reservoir, help to form a network of etching cracks, and increase the volume of carbonate acid fracturing transformation;
[0028] (5) The single-phase slow acid system prepared by the multi-effect nanoemulsion of the present invention can form non-uniform etching, improve the conductivity of acid-etched fractures, and improve the effect of carbonate rock acid fracturing transformation;
[0029] (6) The single-phase slow acid system prepared by the multi-effect nanoemulsion of the present invention has the ability to dissolve both organic and inorganic scales. For reservoirs with organic scale deposits, they can be removed simultaneously in a single step, saving operation time and operation costs;
[0030] (7) The single-phase retarded acid system of the present invention combines the advantages of high retarding rate and low damage of emulsified acid and low friction of thickened acid, overcomes the disadvantages of high friction of emulsified acid and high residue damage of thickened acid, has high retarding rate, low friction and low damage performance, can dissolve organic scale and inorganic scale at the same time, and can eliminate reservoir emulsification, water lock and wettability modification damage, which is of great significance for acidizing and acid fracturing transformation of carbonate reservoirs. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.
[0032] Figure 1 This is a comparison chart of the conductivity of acid-etched cracks in different acid systems. DETAILED DESCRIPTION
[0033] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0034] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] Specifically, the multi-effect nanoemulsion provided by the present invention comprises: an oil core containing a long-chain or cycloalkyl carboxylic acid, a surfactant, an alcohol and a balance of water, and is prepared by the following method:
[0036] (1) In a reaction kettle, an oil core containing a long-chain or cycloalkyl carboxylic acid, alcohol and water are added according to a ratio;
[0037] (2) slowly adding the surfactant into the reaction kettle and stirring slowly;
[0038] (3) The reactor is sealed, stirring and heating are continued, and cooling is performed after the dissolution is complete to obtain a multi-effect nanoemulsion.
[0039] After testing, the multi-effect nanoemulsion of the present invention is a homogeneous nanoemulsion with multiple functions: (1) particle size 8-100 nm; (2) homogeneous system; (3) asphalt solubility rate>85%; (4) surface tension <27mN / m; (5) oil and water are miscible, and the interfacial tension is 0mN / m; (6) wettability modification (oil wetness modification to water wetness).
[0040] The effects and contents of the various components in the multi-effect nanoemulsion of the present invention are described in detail below:
[0041] Oil core containing long chain or cycloalkyl carboxylic acids
[0042] The oil core containing long-chain or cycloalkyl carboxylic acids is used to dissolve organic scale.
[0043] Preferably, the oil core containing long-chain or cycloalkyl carboxylic acid is obtained by the following method: long-chain or cycloalkyl carboxylic acid is mixed with a hydrocarbon solvent in a certain proportion, and there is no requirement for the mixing order.
[0044] Wherein, in the oil core containing long-chain or cycloalkyl carboxylic acid, the content of the long-chain or cycloalkyl carboxylic acid is 5-25wt%; and the content of the hydrocarbon solvent is 75-95wt%.
[0045] Preferably, the proportion of the oil core containing long-chain or cycloalkyl carboxylic acid in the multi-effect nanoemulsion is 5-15wt%. When the proportion of the oil core containing long-chain or cycloalkyl carboxylic acid in the multi-effect nanoemulsion is less than 5wt%, the ability to dissolve asphaltene decreases; when the proportion is greater than 15wt%, the phase stability deteriorates. Among them, when the proportion of the oil core containing long-chain or cycloalkyl carboxylic acid in the multi-effect nanoemulsion is 8-12wt%, the effect is better.
[0046] Further preferably, the long-chain or cycloalkyl carboxylic acid includes one or more of oleic acid, cyclohexylacetic acid, cyclohexylpropionic acid, and cyclohexylvaleric acid.
[0047] Further preferably, the hydrocarbon solvent in the oil core includes one or more of cyclohexane, limonene, and high flash point heavy aromatic hydrocarbons.
[0048] Surfactants
[0049] Surfactants are used to reduce the interfacial tension of liquid surfaces.
[0050] Preferably, the proportion of surfactant in the multi-effect nanoemulsion is 30-50wt%. When the proportion of surfactant in the multi-effect nanoemulsion is less than 30wt%, a stable nanostructure cannot be effectively formed; when the proportion is greater than 50wt%, the viscosity is too high, making preparation and use difficult. Among them, when the proportion of surfactant in the multi-effect nanoemulsion is 35-45wt%, the effect is better.
[0051] Further preferably, the surfactant includes: one or more of tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, fatty alcohol polyoxyethylene ether, sodium lauryl sulfate, and styrylphenol polyoxyethylene ether.
[0052] alcohol
[0053] Used to assist surfactants in forming nanoemulsions while reducing liquid viscosity.
[0054] Preferably, the proportion of alcohol in the multi-effect nanoemulsion is 10-30wt%. When the proportion of alcohol in the multi-effect nanoemulsion is less than 10wt%, the viscosity is too high, and it is difficult to prepare and use; when the proportion is greater than 30wt%, the concentration of other components is low, and it is difficult to form a nanoemulsion structure. Among them, when the proportion of alcohol in the multi-effect nanoemulsion is 15-25wt%, the effect is better.
[0055] More preferably, the alcohol includes one or more of n-pentanol, isopropanol, propylene glycol and n-octanol.
[0056] In the multi-effect nanoemulsion of the present invention, each component plays a synergistic role to make it have multiple functions. Specifically, the oil core containing long-chain or alkyl carboxylic acid in the multi-effect nanoemulsion has a strong solubility for organic scale, and the asphalt dissolution rate is above 85%. The surfactant in the multi-effect nanoemulsion can greatly reduce the surface interfacial tension, the surface tension is below 27mN / m, the oil and water are miscible, the interfacial tension is 0mN / m, and the water lock damage can be relieved. The present invention greatly reduces the acid-rock reaction rate by adsorbing the oil core containing long-chain or alkyl carboxylic acid and the surfactant on the rock surface in the multi-effect nanoemulsion, and the slowing rate is above 90%; further, by adsorbing the surfactant on the rock surface, the rock surface is modified from oil-wet to water-wet, reducing the flow resistance of crude oil and increasing the crude oil yield.
[0057] On the other hand, the present invention also provides a method for using the multi-effect nanoemulsion, comprising: mixing the multi-effect nanoemulsion, hydrochloric acid, a corrosion inhibitor, an iron ion stabilizer, a demulsifier, a drag reducing agent and water in proportion, and stirring at 10-40° C. for 0.5-1 hour to obtain a single-phase slow acid system.
[0058] After testing, the single-phase retarding acid system of the present invention has the following properties: (1) retarding rate>90%; (2) demulsification rate>90%; (3) drag reduction rate>70%; (4) asphalt dissolution rate>5%; (5) it can dissolve organic scale and inorganic scale at the same time, and can relieve reservoir emulsification, water lock, and wetting modification damage.
[0059] The following is a detailed introduction to the functions and contents of each component in the single-phase retarded acid system:
[0060] Multi-effect nanoemulsion
[0061] Multi-effect nanoemulsion is used to remove organic matter adsorbed on the rock surface, while releasing long-chain or cycloalkyl carboxylic acids in the oil core, isolating the acid from the rock and reducing the acid-rock reaction rate.
[0062] The weight percentage of the multi-effect nanoemulsion in the single-phase slow acid system is 1%-20%, preferably 2-10%.
[0063] The components and contents of the multi-effect nanoemulsion are detailed in the above disclosure, and the present invention will not repeat them here.
[0064] hydrochloric acid
[0065] Hydrochloric acid is used to dissolve rocks and achieve the purpose of reservoir transformation.
[0066] The weight percentage of hydrochloric acid in the single-phase slow acid system is 5%-25%, preferably 10-20%.
[0067] Corrosion Inhibitor
[0068] Corrosion inhibitors are used to reduce tubing corrosion.
[0069] The weight percentage of the corrosion inhibitor in the single-phase slow-rate acid system is 0.5%-3%, preferably 1-2%.
[0070] Further preferably, the corrosion inhibitor includes: one or more of pyridinium quaternary ammonium salt corrosion inhibitors, quinoline quaternary ammonium salt corrosion inhibitors and imidazoline corrosion inhibitors.
[0071] Iron ion stabilizer
[0072] Iron ion stabilizer is used to stabilize iron ions and prevent secondary precipitation damage.
[0073] The weight percentage of the iron ion stabilizer in the single-phase slow acid system is 0.5%-2%, preferably 0.75-1.5%.
[0074] Further preferably, the iron ion stabilizer includes one or more of citric acid, ethylenediaminetetraacetic acid and isoascorbic acid.
[0075] Demulsifier
[0076] Demulsifiers are used to prevent crude oil from emulsifying and improve the permeability of fluids in rocks.
[0077] The weight percentage of the demulsifier in the single-phase slow acid system is 0.5%-2%, preferably 0.75-1.5%.
[0078] Further preferably, the demulsifier includes: one or more of sodium dioctyl sulfonate, polyoxyethylene ether, and dialkyl succinate.
[0079] Drag reducing agent
[0080] The friction reducing agent is used to reduce the friction resistance of the acid in the pipe string and reduce the equipment load.
[0081] The weight percentage of the drag reducing agent in the single-phase retarding acid system is 0.1%-0.8%, preferably 0.1-0.5%.
[0082] Further preferably, the drag reducing agent includes one or more of cationic polyacrylamide, polysaccharide polymers and vinyl polymers.
[0083] The invention discloses a method for using a multi-effect nanoemulsion for a single-phase retarding acid system, wherein the multi-effect nanoemulsion is added to an acid solution in a certain proportion to form a single-phase retarding acid system. The single-phase retarding acid system combines the advantages of high retarding rate and low damage of emulsified acid and low friction resistance of thickened acid, overcomes the disadvantages of high friction resistance and high residue damage of emulsified acid, has high retarding rate (retarding rate is above 90%), low friction resistance (drag reduction rate is above 70%), and low damage performance (low polymer residue), can dissolve organic scale and inorganic scale (asphalt dissolution rate is above 5%, carbonate rock dissolution rate is 100%) at the same time, and can remove reservoir emulsification (emulsification rate is above 90%), water lock (interfacial tension is below 3mN / m), and wettability modification damage (oil wet is modified to water wet), and is of great significance for acidification and acid fracturing transformation of carbonate reservoirs.
[0084] Example
[0085] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions. The raw materials used in the following examples are all conventionally purchased.
[0086] Example 1
[0087] Preparation of the first liquid: In a ceramic reactor, add 4 g of cyclohexane, 4 g of cyclohexylpropionic acid, 20 g of isopropanol and 32 g of water.
[0088] Preparation of the second liquid: In a ceramic reaction kettle, add 20 g of fatty alcohol polyoxyethylene ether, 10 g of styrylphenol polyoxyethylene ether, and 10 g of tetradecyltrimethylammonium bromide, turn on the stirrer, and stir slowly.
[0089] Compounding: Seal the reactor and continue stirring. When it is heated to 50°C by steam, the reaction temperature is controlled at about 50°C by the automatic control system. The pressure in the reactor does not need to be controlled and does not exceed 1.0MPa. After 2 hours, after the dissolution is complete, pass circulating water for cooling. When the temperature reaches below 30°C, discharge it from the bottom of the reactor to obtain 100g of a single-phase retarded acid system with multiple effects nanoemulsion.
[0090] The particle size of the multi-effect nanoemulsion is 10-80nm, it is a homogeneous system, the asphalt dissolution rate is 88.92% at 90°C for 4 hours, the surface tension is 26.54mN / m, the interfacial tension is 0mN / m, and the wetting angle is 20°.
[0091] Take the multi-effect nanoemulsion to prepare a single-phase retarded acid system, mix 5% of the multi-effect nanoemulsion, 15% of hydrochloric acid, a corrosion inhibitor, 1% of an iron ion stabilizer, 1% of a demulsifier, 0.1% of a resistance reducing agent and 77.9% of water in proportion, and stir at 10-40° C. for 0.5-1 hour to obtain a single-phase retarded acid system.
[0092] The single-phase retarded acid system is a homogeneous system with a particle size of 10-80nm, a retarding rate of 92.56%, a demulsification rate of 99%, a drag reduction rate of 75%, an asphalt dissolution rate of 6.91% in 4h at 90℃, a calcium carbonate dissolution rate of 100% in 4h at 90℃, an interfacial tension of 2.85mN / m, and a wetting angle of 68°.
[0093] Example 2
[0094] Preparation of the first liquid: In a ceramic reactor, add 5 g of cyclohexane, 5 g of cyclohexylpropionic acid, 20 g of isopropanol and 30 g of water.
[0095] Preparation of the second liquid: In a ceramic reactor, add 20 g of fatty alcohol polyoxyethylene ether, 10 g of styrylphenol polyoxyethylene ether, and 10 g of tetradecyltrimethylammonium bromide, turn on the stirrer, and stir slowly.
[0096] Compounding: Seal the reactor and continue stirring. When it is heated to 50°C by steam, the reaction temperature is controlled at about 50°C by the automatic control system. The pressure in the reactor does not need to be controlled and does not exceed 1.0MPa. After 2 hours, after the dissolution is complete, pass circulating water for cooling. When the temperature reaches below 30°C, discharge it from the bottom of the reactor to obtain 100g of a single-phase retarded acid system with multiple effects nanoemulsion.
[0097] The particle size of the multi-effect nanoemulsion is 10-80nm, it is a homogeneous system, the asphalt dissolution rate is 90.22% at 90°C for 4 hours, the surface tension is 26.44mN / m, the interfacial tension is 0mN / m, and the wetting angle is 21°.
[0098] Take the multi-effect nanoemulsion to prepare a single-phase retarded acid system, mix 5% of the multi-effect nanoemulsion, 15% of hydrochloric acid, a corrosion inhibitor, 1% of an iron ion stabilizer, 1% of a demulsifier, 0.1% of a resistance reducing agent and 77.9% of water in proportion, and stir at 10-40° C. for 0.5-1 hour to obtain a single-phase retarded acid system.
[0099] The single-phase retarded acid system is a homogeneous system with a particle size of 10-80nm, a retarding rate of 93.32%, a demulsification rate of 99%, a drag reduction rate of 75%, an asphalt dissolution rate of 8.28% at 90°C for 4h, a calcium carbonate dissolution rate of 100% at 90°C for 4h, an interfacial tension of 2.87mN / m, and a wetting angle of 69°.
[0100] Comparative Example 1: Emulsified Acid
[0101] Prepare an emulsified acid system, oil phase: acid phase = 3:7, oil phase: 93% diesel + 7% emulsifier, acid phase: 21.4% HCL + 2% corrosion inhibitor + 1% iron stabilizer;
[0102] The diesel oil is -10# industrial diesel oil; the emulsifier is WD-31 emulsifier, purchased from Chengdu Anshide Petroleum Technology Development Co., Ltd.; HCL is 31% industrial hydrochloric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; the corrosion inhibitor is Mannich base quaternary ammonium salt corrosion inhibitor (high temperature acidification corrosion inhibitor), purchased from Tianjin Juli Polymer Petroleum Engineering Technology Co., Ltd.; the iron stabilizer is citric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd. Emulsified acid performance: the retarding rate is 94.12%, the friction resistance is high (the friction resistance is 150% of clean water); the organic scale dissolving ability is weak (the asphalt dissolution rate is 1.24% at 90°C for 4 hours).
[0103] Comparative Example 2: Thickened Acid
[0104] Prepare a cross-linked acid system: 15% HCL + 1% thickener + 1% cross-linker + 2% corrosion inhibitor + 1% iron stabilizer + 1% drainage aid + 1% demulsifier;
[0105] HCL is 31% industrial hydrochloric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; the thickener is PA-CDA thickener, purchased from Tianjin COSL Chemical Co., Ltd.; the crosslinker is PA-CDB crosslinker, purchased from Tianjin COSL Chemical Co., Ltd.; the corrosion inhibitor is Mannich base quaternary ammonium salt corrosion inhibitor (high temperature acidification corrosion inhibitor), purchased from Tianjin Juli Polymer Petroleum Engineering Technology Co., Ltd.; the iron stabilizer is citric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; the drainage agent is a fluorocarbon surfactant (C8F 17 SO2NHC3H7NR2(O)), purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; demulsifier is nonylphenol polyoxyethylene ether (C 15 H 24 O(C2H4O) n ), purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.
[0106] Thickened acid performance: retarding rate is 80.4%, drag reduction rate is 60%; no asphalt dissolving ability.
[0107] Comparative Example 3: Clean Steering Acid
[0108] Prepare the steering acid system, 15% HCL + 6% VES + 1% special corrosion inhibitor + 1% iron stabilizer;
[0109] HCL is 31% industrial hydrochloric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; VES is VES-1 viscoelastic surfactant, purchased from Beijing Comes Oilfield Chemical Technology Co., Ltd.; special corrosion inhibitor is viscoelastic surfactant special corrosion inhibitor, purchased from Beijing Comes Oilfield Chemical Technology Co., Ltd.; iron stabilizer is citric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.
[0110] Clean steering acid performance: retarding rate is 70.9%, drag reduction rate is 50%; no asphalt dissolving ability.
[0111] Performance Testing
[0112] Experimental evaluation of residual acid damage to reservoir physical properties
[0113] The damage of the residual acid in the single-phase slow acid system to the reservoir properties in Example 1 was evaluated, and thickened acid, emulsified acid, and clean diverting acid were used as comparisons.
[0114] Experimental steps:
[0115] 1. The core is washed with oil and salt;
[0116] 2. Evacuate for 6 hours, saturate with 2wt% KCl for 12 hours, and place in a holder to displace 2PV;
[0117] 3. Use the treated kerosene to displace the core to create bound water until the kerosene pressure is stable and the liquid output is stable, and K1 is obtained.
[0118] 4. Forward displacement of residual acid at a constant pressure of 10 MPa for 120 minutes, then stop the pump to allow the pressure to recover naturally for 6 hours;
[0119] 5. Reverse displacement of kerosene until the kerosene pressure is stable and K2 is obtained;
[0120] 6. Calculate the damage rate of different residual acids to the core;
[0121] It can be seen from the experimental results that the residual acid damage rate of the single-phase slow acid system to the core is much lower than that of the thickened acid, and lower than that of the emulsified acid and the clean diverting acid.
[0122] Table 1 Damage rate of different residual acids to core
[0123]
[0124] Acid-etched crack conductivity test experiment
[0125] The conductivity of the acid-etched fractures of the single-phase slow acid system in Example 1 was evaluated, and thickened acid and emulsified acid were used for comparison. The experimental scheme is shown in Table 2, the experimental temperature is 70°C, and the experimental displacement is set at 100 mL / min. The pre-fluid used for alternating injection acid fracturing is all viscous and slippery water.
[0126] The experimental results are shown in Figure 1 The experimental results show that the conductivity of single-phase retarded acid is not in the same order of magnitude as that of thickened acid and emulsified acid, which reflects the importance of etching mode. Uniform etching has partial conductivity at low closing pressure, and the conductivity drops sharply to almost zero as the pressure increases. Single-phase retarded acid can form non-uniform etching and still has high conductivity under high closing stress.
[0127] Table 2 Experimental scheme for conductivity of acid-etched cracks
[0128]
[0129] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.
Claims
1. A multi-effect nanoemulsion, characterized in that: Calculated by weight percentage, it includes: 5%-15% of an oil core containing a long-chain or cycloalkyl carboxylic acid, 30%-50% of a surfactant, 10%-30% of an alcohol, and the balance of water; The oil core containing long-chain or cycloalkyl carboxylic acid is obtained by the following method: long-chain or cycloalkyl carboxylic acid and hydrocarbon solvent are mixed in a certain proportion; wherein the content of the long-chain or cycloalkyl carboxylic acid is 5-25wt%; the content of the hydrocarbon solvent is 75-95wt%; Wherein, the long-chain or cycloalkyl carboxylic acid includes one or more of cyclohexyl acetic acid, cyclohexyl propionic acid, and cyclohexyl valeric acid; the hydrocarbon solvent is cyclohexane; Wherein, the surfactant composition is: tetradecyl trimethyl ammonium bromide, fatty alcohol polyoxyethylene ether, styrylphenol polyoxyethylene ether; Wherein, the alcohol includes: one or more of n-pentanol, isopropanol, and n-octanol.
2. The method for preparing the multi-effect nanoemulsion according to claim 1, characterized in that: The following steps are involved: (1) In a reaction kettle, an oil core containing a long-chain or cycloalkyl carboxylic acid, alcohol and water are added according to a ratio; (2) slowly adding the surfactant into the reaction kettle and stirring slowly; (3) The reactor is sealed, stirring and heating are continued, and cooling is performed after the dissolution is complete to obtain a multi-effect nanoemulsion.
3. The method for preparing the multi-effect nanoemulsion according to claim 2, characterized in that, The heating temperature is 40-60°C; the cooling temperature is below 30°C.
4. The method for using the multi-effect nanoemulsion according to claim 1, characterized in that: include: The multi-effect nanoemulsion, hydrochloric acid, corrosion inhibitor, iron ion stabilizer, demulsifier, drag reducing agent and water are mixed in proportion, and stirred at 10-40° C. for 0.5-1 hour to obtain a single-phase slow-rate acid system.
5. The method for using the multi-effect nanoemulsion according to claim 4, characterized in that: By weight percentage, the single-phase slow-rate acid system comprises: 1%-20% multi-effect nanoemulsion, 5%-25% hydrochloric acid, 0.5%-3% corrosion inhibitor, 0.5%-2% iron ion stabilizer, 0.5%-2% demulsifier, 0.1%-0.8% drag reducing agent and the balance water.
6. The method for using the multi-effect nanoemulsion according to claim 4, characterized in that: The corrosion inhibitor includes: one or more of pyridine quaternary ammonium salt corrosion inhibitor, quinoline quaternary ammonium salt corrosion inhibitor and imidazoline corrosion inhibitor; the iron ion stabilizer includes: one or more of citric acid, ethylenediaminetetraacetic acid and isoascorbic acid; the demulsifier includes: one or more of sodium dioctyl diacid sulfonate, polyoxyethylene ether, and dialkyl succinate; the drag reducing agent includes: one or more of cationic polyacrylamide, polysaccharide polymer and ethylene polymer.
7. Use of the multi-effect nanoemulsion according to claim 1 in acidizing and fracturing of carbonate reservoirs.
Citation Information
Patent Citations
High-temperature-resisting emulsified acid liquid
CN104194767A
High-temperature-resistant cross-linking acid system, preparation method and applications thereof
CN107974246A
Micro-lactic acid blocking removal system and preparation method thereof
CN114316935A
Preparation method of microemulsion type discharge aiding agent for fracturing high rank coal
CN108559478A
High-efficiency variable-viscosity fracturing fluid for deep coal bed gas development and integrated construction method
CN116200183A